2020
DOI: 10.1177/1350650120949082
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of thermal dynamic micro-EHL considering bearing assembly temperature

Abstract: To investigate thermal failure of dynamic oil film in cylindrical roller bearings(CRBs), based on the temperature field of CRBs, non-Newtonian dynamic thermal elastohydrodynamic (TEHL) lubricating performance in cylindrical roller bearings was conducted. A single surface bump was coupled with longitudinal waviness on the roller surface, and a dynamic non-Newtonian finite line contact TEHL model was established considering the boundary temperature of the bearing assembly. Effects of the roller boundary temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…For example, Cui et al 14 investigated the dynamic contact behavior of the hydrodynamic journal bearing during the start-up, the hydrodynamic oil force and asperity contact force are all considered. Liu et al 15 established a thermal elastohydrodynamic lubrication (TEHL) model considering the boundary temperature of the bearing. Wang et al 16 combined bearing dynamics and thermal EHL method and they found that under a certain bearing speed, the lubrication performance will deteriorate when an inappropriate axial load is applied.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cui et al 14 investigated the dynamic contact behavior of the hydrodynamic journal bearing during the start-up, the hydrodynamic oil force and asperity contact force are all considered. Liu et al 15 established a thermal elastohydrodynamic lubrication (TEHL) model considering the boundary temperature of the bearing. Wang et al 16 combined bearing dynamics and thermal EHL method and they found that under a certain bearing speed, the lubrication performance will deteriorate when an inappropriate axial load is applied.…”
Section: Introductionmentioning
confidence: 99%
“…Many foreign and native scholars have conducted a lot of research on the lubrication characteristics of the contact area of cylindrical roller bearings. Qiu et al [10][11][12][13] calculated the dynamic characteristics of the cylindrical roller bearing contact micro-zone, calculated the oil film thickness and analyzed the bearing lubrication characteristics by using the quasistatic method and the elastohydrodynamic lubrication (EHL) model. The thermal effect, non-Newtonian and other factors were considered based on the Dowson empirical formula by Marian et.al [14].…”
Section: Introductionmentioning
confidence: 99%
“…Alfares et al 26 built a coupling model of thermal analysis with dynamics for machine tool spindle-bearing system to research the effect of speed, temperature and lubricant on thermal condition of bearing system. Liu et al 27 presented a thermal EHL analysis model and investigated the influence of boundary temperature and surface bump of roller on thermal failure of bearing. Fang et al 28 proposed a mixed thermal EHL model for ball bearing with wear zone to investigate the lubricating characteristics including film thickness, pressure and interfacial temperature.…”
Section: Introductionmentioning
confidence: 99%